The influence of successive matches on match-running performance during an under-23 international soccer tournament: The necessity of individual analysis - Varley, M. C.; Di Salvo, V.; Modonutti, M.; Gregson, W.; Mendez-Villanueva, A. (Journal of Sports Sciences, 2018)
This study investigated the effects of successive matches on match-running in elite under-23 soccer players during an international tournament. Match-running data was collected using a semi-automated multi-camera tracking system during an international under-23 tournament from all participating outfield players. Players who played 100% of all group stage matches were included (3 matches separated by 72 h, n = 44). Differences in match-running performance between matches were identified using a generalised linear mixed model. There were no clear effects for total, walking, jogging, running, high-speed running and sprinting distance between matches 1 and 3 (effect size (ES); -0.32 to 0.05). Positional analysis found that sprint distance was largely maintained from matches 1 to 3 across all positions. Attackers had a moderate decrease in total, jogging and running distance between matches 1 and 3 (ES; -0.72 to -0.66). Classifying players as increasers or decreasers in match-running revealed that match-running changes are susceptible to individual differences. Sprint performance appears to be maintained over successive matches regardless of playing position. However, reductions in other match-running categories vary between positions. Changes in match-running over successive matches affect individuals differently; thus, players should be monitored on an individual basis.